2018
DOI: 10.1186/s12955-018-0893-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in pediatric and adolescent patients with transfusion-dependent ß-thalassemia in upper Egypt (single center study)

Abstract: BackgroundThalassemia is a major health problem that disturbs the lifestyle of the affected patient. The aim of this work is to detect the impact of thalassemia on the quality of life regarding physical, social, emotional, psychological scored assessment.MethodsA case-control survey was conducted in Minia University children’s hospital on 64 patients recruiting pediatric hematology outpatient clinic from July 2014 to February 2017. PedsQL™ 4.0 Generic Core Scale (Arabic version) was used to assess HRQOL in 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
26
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 29 publications
9
26
1
4
Order By: Relevance
“…This suggests that the improvements in medical care may not have contributed substantially to upgrade the quality of life of these patients. However, the quality of life scores reported in these studies are significantly higher than the scores reported among patients in Egypt [29]. This is probably due to the difference in the clinical management where patients in south and southeast Asia receiving better levels of transfusion and chelation compared to patients in Africa.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This suggests that the improvements in medical care may not have contributed substantially to upgrade the quality of life of these patients. However, the quality of life scores reported in these studies are significantly higher than the scores reported among patients in Egypt [29]. This is probably due to the difference in the clinical management where patients in south and southeast Asia receiving better levels of transfusion and chelation compared to patients in Africa.…”
Section: Discussioncontrasting
confidence: 58%
“…Secondly, we compared the HRQoL scores of patients with β-thalassaemia with that of healthy controls therefore, a generic questionnaire was deemed more suitable. Also, PedsQL 4.0 questionnaire was easy to use and has been widely used among patients with thalassaemia previously [20,29].…”
Section: Discussionmentioning
confidence: 99%
“…The Psychosocial Health Summary Score was consistently found to be lower compared to the Physical Health Summary Score in previous studies conducted in Malaysia [7][8][9], Thailand [10][11][12] or the Middle East [16,31,32]. We found that the school functioning dimension had the lowest mean score in this study.…”
Section: Discussionsupporting
confidence: 51%
“…The Psychosocial Health Summary Score was consistently found to be lower compared to the Physical Health Summary Score in previous studies conducted in Malaysia(7-9), Thailand (10)(11)(12) or the Middle East (16,31,32). We found that the school functioning dimension had the lowest mean score in this study.…”
Section: Discussionsupporting
confidence: 52%